Aberrant Expression of Circulating MicroRNA Leads to the Dysregulation of Alpha-Synuclein and Other Pathogenic Genes in Parkinson’s Disease - Cai, Meng; Chai, Songshan; Xiong, Tao; Wei, Jun; Mao, Weibing; Zhu, Yasha; Li, Xiang; Wei, Wei; Dai, Xuan; Yang, Bangkun; Liu, Wen; Shu, Bing; et al. (Frontiers in Cell and Developmental Biology, 2021)
Abstract: A group of circulating microRNAs have been implicated in the pathogenesis of Parkinson’s disease. However, a full picture of the interactions between the pathogenic microRNAs and their downstream Parkinson’s disease (PD)-related target genes has not been investigated. Here, we identified the microRNA expression profiles in the plasma and circulating exosomes of Parkinson’s disease patients using next generation RNA sequencing. KEGG (Kyoto Encyclopedia of Genes and Genomes) and GO (Gene Ontology) analysis showed that the microRNA target genes were enriched in axon guidance, neurotrophin signaling, cellular senescence, as well as TGF-beta, MAPK, PI3K-Akt and mTOR signaling pathways. Furthermore, a group of aberrantly expressed microRNAs were selected and further validated in the individual patient plasma as well as human neural stem cell and rat model of Parkinson’s disease. More importantly, the regulatory network between these microRNAs and their PD-related gene targets was examined in a fully scale in human neural stem cells and revealed a similar but still varied downstream regulatory cascade involving many known PD associated genes. Additionally, the miR-23b-3p was identified as a novel direct regulator of alpha synuclein, the possible culprit in the Parkinson’s disease. Our current study, for the first time, provided a glimpse into the regulatory network of pathogenic microRNAs and their PD-related gene targets in Parkinson’s disease. Moreover, these PD associated microRNAs may serve as the biomarkers and novel therapeutic targets for Parkinson’s disease.